(untitled) (Eurasian Scientific Herald, 2024)
According to previous reviews, breast cancer is one of the most common malignant tumors among women. Although the causes of breast cancer are many and not fully understood, exposure to Epstein-Barr virus (EBV) can be suggested as a risk factor for breast cancer. Studies since 1995 have reported that the EBV virus is directly involved in the development of breast cancer.